PENGARUH LEARNING AGILITY, CHANGE AGILITY, MENTAL AGILITY, DAN RESULT AGILITY PADA GURU MADRASAH DINIYAH: PENGARUH LEARNING AGILITY, CHANGE AGILITY, MENTAL AGILITY, DAN RESULT AGILITY PADA GURU MADRASAH DINIYAH - M. Jamhuri; Nizar, Muhammad; Riyanto (JIPSKi: Jurnal Ilmu Pendidikan dan Studi Keislaman, 2024)
This research aims to analyze the influence of people agility, change agility, mental agility, and result agility on Madrasah Diniyah teachers in Tutur Subdistrict, Pasuruan Regency. The researcher used a survey method distributed via a Google Form questionnaire. The population of this study consists of Madrasah Diniyah teachers, with a sample of 117 people obtained using random sampling techniques. The data were analyzed descriptively and measured using the analysis of variance (ANOVA) test assisted by the SPSS 22 program. The results of the study show that Madrasah Diniyah teachers in Tutur Subdistrict have a high level of agility in performing their duties. More than 60% of respondents showed positive responses to current developments and applied agility in their work. Based on the research results, teachers with high agility demonstrated maximum performance, were able to draw lessons from work experiences, adapted to changes with full awareness and enthusiasm for learning to improve their skills, knowledge, and competence. Based on gender classification, there was no significant difference between male and female teachers in the application of agility. This study provides insight that the development of agility in teachers can significantly contribute to improving the quality of education in Madrasah Diniyah.